Learning Commons: Konsep Pengembangan Perpustakaan Perguruan Tinggi Menghadapi Generasi Digital - Muhammad Choironi Yusuf (Pustakaloka, 2015)
n the digital age, when information can be accessed without any  limits  of  space  and  time,  has  given  the  considerable  impact  of the  library. During  this  period,  the  existence  of  library  started  to  be questioned. Information search behavior changes and the changing needs of the library makes a librarian sued to be able to keep abreast of the latest developments  in managing a  library. To answer  this need,  the  idea of learning commons appears, by changing the concept of management of libraries that are adapted to the character of the digital generation. The concept of learning commons present  in an efort to ofset any change in  behavior  of  the  digital  generation  in utilizing  community  library. Creating  Library  learning  commons-based  does  not mean  having  to pay, but the most important is how to change the mindset of librarian.